Silencing of Chemosensory Protein Gene NlugCSP8 by RNAi Induces Declining Behavioral Responses of Nilaparvata lugens - Waris, Muhammad I.; Younas, Aneela; ul Qamar, Muhammad T.; Hao, Liu; Ameen, Asif; Ali, Saqib; Abdelnabby, Hazem Elewa; Zeng, Fang-Fang; Wang, Man-Qun (Frontiers in Physiology, 2018)
Chemosensory proteins (CSPs) play imperative functions in chemical and biochemical signaling of insects, as they distinguish and transfer ecological chemical indications to a sensory system in order to initiate behavioral responses. The brown planthopper (BPH), Nilaparvata lugens Stål (Hemiptera: Delphacidae), has emerged as the most destructive pest, causing serious damage to rice in extensive areas throughout Asia. Biotic characteristics like monophagy, dual wing forms, and annual long-distance migration imply a critical role of chemoreception in N. lugens. In this study, we cloned the full-length CSP8 gene from N. lugens. Protein sequence analysis indicated that NlugCSP8 shared high sequence resemblance with the CSPs of other insect family members and had the typical four-cysteine signature. Analysis of gene expression indicated that NlugCSP8 mRNA was specifically expressed in the wings of mated 3-day brachypterous females with a 175-fold difference compare to unmated 3-day brachypterous females. The NlugCSP8 mRNA was also highly expressed in the abdomen of unmated 5-day brachypterous males and correlated to the age, gender, adult wing form, and mating status. A competitive ligand-binding assay demonstrated that ligands with long chain carbon atoms, nerolidol, hexanal and trans-2-hexenal were able to bind to NlugCSP8 in declining order of affinity. By using bioinformatics techniques, three-dimensional protein structure modeling and molecular docking, the binding sites of NlugCSP8 to the volatiles which had high binding affinity were predicted. In addition, behavioral experiments using the compounds displaying the high binding affinity for the NlugCSP8, revealed four compounds able to elicit significant behavioral responses from N. lugens. The in vivo functions of NlugCSP8 were further confirmed through the testing of RNAi and post-RNAi behavioral experiments. The results revealed that reduction in NlugCSP8 transcript abundance caused a decrease in behavioral response to representative attractants. An enhanced understanding of the NlugCSP8 is expected to contribute in the improvement of more effective and eco-friendly control strategies of BPH.